2019
DOI: 10.1177/1948550619856302
|View full text |Cite
|
Sign up to set email alerts
|

On Trust and Disgust: Evidence From Face Reading and Virtual Reality

Abstract: We report three studies exploring the relationship between disgust and trust. Study 1a measured emotions using face-reading technology while participants played a repeated trust game. We observed a negative correlation between trust and disgust. Study 1b employed self-reports along with the face reader. The self-report procedure adversely affected participants’ emotional state and eliminated the correlation between trust and other emotions. Study 2 induced incidental disgust or sadness using virtual reality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…These results are in line with theory and findings suggesting that cooperation, in general, is intuitively driven (e.g., Halevy & Chou, 2014;Levine et al, 2018;Rand, 2016;Rand et al, 2012, but see Bouwmeester et al, 2017;Tinghög et al, 2013). These results are also consistent with behavioral (Kugler et al, 2020;Pillutla & Murnighan, 1996), physiological (van't Wout et al, 2006, and neurological (Sanfey et al, 2003;Tabibnia et al, 2008;van den Bos et al, 2009) studies indicating that visceral, automatically driven emotions are involved in fair and reciprocal behavior (for a review, see Sanfey & Chang, 2008). Additionally, cognitive control processes, in the form of emotion regulation, are required in order to override and downregulate these automatic emotional processes (Bereby-Meyer et al, 2009;Gilam et al, 2015;Grecucci et al, 2013;Tabibnia et al, 2008;van 't Wout et al, 2010;Xiao & Houser, 2005).…”
Section: Reciprocity Self-interest and Cognitive Controlsupporting
confidence: 92%
“…These results are in line with theory and findings suggesting that cooperation, in general, is intuitively driven (e.g., Halevy & Chou, 2014;Levine et al, 2018;Rand, 2016;Rand et al, 2012, but see Bouwmeester et al, 2017;Tinghög et al, 2013). These results are also consistent with behavioral (Kugler et al, 2020;Pillutla & Murnighan, 1996), physiological (van't Wout et al, 2006, and neurological (Sanfey et al, 2003;Tabibnia et al, 2008;van den Bos et al, 2009) studies indicating that visceral, automatically driven emotions are involved in fair and reciprocal behavior (for a review, see Sanfey & Chang, 2008). Additionally, cognitive control processes, in the form of emotion regulation, are required in order to override and downregulate these automatic emotional processes (Bereby-Meyer et al, 2009;Gilam et al, 2015;Grecucci et al, 2013;Tabibnia et al, 2008;van 't Wout et al, 2010;Xiao & Houser, 2005).…”
Section: Reciprocity Self-interest and Cognitive Controlsupporting
confidence: 92%
“…Controlled variations in identity, appearance and proximity create new possibilities in studies of discrimination (Peck et al 2013) and the use of virtual humans avoids the reflection problem in studies of peer effects (Gürerk et al 2019). Realistic but controllable environments further allow for strong emotion induction in studies on moral judgements (Kugler et al 2019) and for measurement of responses that would be impossible or unethical to obtain in any other way, such as evacuation behavior of non-experts (Kinateder et al 2014) and the trolley problem (Navarrete et al 2012). For a more extensive review of the possibilities and drawbacks for high-immersive VR experiments in economics the reader is referred to Mol (2019).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Some research has found disgust (physical or interpersonal) to be related to harsher moral judgments (Eskine et al, 2011;Schnall et al, 2008) and a desire for purity (Horberg et al, 2009). People primed with disgust judge unethical behaviors more harshly (Schnall et al, 2008;Wheatley & Haidt, 2005) and are less trusting (Kugler et al, 2020). Scenarios designed to evoke strong disgust are perceived as unethical (Haidt et al, 1993).…”
Section: Discussionmentioning
confidence: 99%